The effect of exercise on resting concentrations of peripheral brain-derived neurotrophic factor (BDNF) in major depressive disorder: A meta-analysis. (October 2018) - Dinoff, Adam; Herrmann, Nathan; Swardfager, Walter; Gallagher, Damien; Lanctôt, Krista L.
Abstract: Exercise interventions have been shown to successfully improve depression in patients with major depressive disorder (MDD), but like other forms of antidepressant treatment, exercise is not effective in all patients and its mechanisms of action have not been fully elucidated. Brain-derived neurotrophic factor (BDNF), a key mediator of neurogenesis and neuronal survival, has been shown to be decreased in individuals with MDD. One potential mechanism by which exercise alleviates depression is through an increase in BDNF. In order to evaluate this hypothesis, we conducted a meta-analysis of studies that assessed the effects of a chronic (multi-week) exercise intervention on BDNF concentrations in MDD patients. MEDLINE, Embase, PsycINFO, SPORTDiscus, Rehabilitation & Sports Medicine Source, and CINAHL databases were searched for original, peer-reviewed reports of peripheral blood BDNF concentrations before and after a chronic exercise intervention in MDD patients. Standardized mean differences (SMDs) were generated from random effects models. Potential sources of heterogeneity were explored in meta-regression analyses. In six studies that met inclusion criteria, resting blood concentrations of BDNF were not significantly higher after a chronic exercise intervention (SMD = 0.43, 95% CI: −0.06–0.92, p = 0.09) in MDD patients. This meta-analysis did not find evidence that a chronic aerobic exercise intervention increases resting concentrations of BDNF in the blood of MDD patients; however, there is a lack of studies in this area making it difficult to reach a definitive conclusion. Future studies on this topic with larger sample sizes and longer durations are needed to draw more robust conclusions.